Somethingtofoodabout : exploring creativity with innovative chefs - Questlove (Clarkson Potter/Publishers, 2016)
"The frontman of hip-hop stars The Roots and bandleader for Jimmy Fallon's The Tonight Show draws on conversations with 10 cutting-edge chefs, including Ludo Lefebvre, Dominique Crenn and Nathan Myrfvold, to offer inspirational insights into their creative culinary processes,"--NoveList.